Effect of Needle Milling Modes on Machining Productivity - I. L. Barshaj (Наука и техника)
The paper presents results of experimental research pertaining to effect of needle milling modes on productivity.It has been ascertained that rates of cutting Vt tension i and micro cutting tool sweep L make an effect on machining productivity.It is revealed that the indicated machining modes are to be considered as the most optimum ones •which permit to obtain maximum productivity.